Reducing Aortic Barotrauma and Vascular Extracellular Matrix Degradation by Pacemaker‐Mediated QRS Widening. Issue 10 (18th May 2020) - Sezer, Murat; Atici, Adem; Coskun, Isa; Cizgici, Yaşar; Ozcan, Alp; Umman, Berrin; Bugra, Zehra; Ozcan, Ilke; Hasdemir, Hakan; Kocaaga, Mehmet; Davies, Justin E.; Umman, Sabahattin
Abstract : Background: The extent of pressure‐related damage might be related to acceleration rate of the applied pressure (peak dP/dt) in the vascular system. In this study, we sought to determine whether dP/dt applied to the aortic wall (aortic dP/dt) and in turn vascular extracellular matrix degradation can be mitigated via modulation of left ventricular (LV) contractility (LV dP/dt) by pacemaker‐mediated desynchronization. Methods and Results: First, in 34 patients, changes in aortic dP/dt values in 3 aortic segments in response to pacemaker‐mediated stepwise QRS widening leading to gradual desynchronization of the LV contraction by means of steadily changed atrioventricular delay (AVD) with temporary dual‐chamber pacing was examined before and after beta‐blocker (15 mg IV metoprolol) administration. Second, serum matrix metalloproteinase‐9 levels were measured in the 20 patients with permanent pacemaker while they were on sinus rhythm with normal QRS width and 3 weeks after wide QRS rhythm ensured by dual pacing, dual sensing, and dual response to sensing with short AVD. LV dP/dt substantially correlated with dP/dt measured in ascending ( r =0.83), descending ( r =0.89), and abdominal aorta ( r =0.96). QRS width strongly correlated with dP/dt measured in ascending ( r =−0.95), descending ( r =−0.92), and abdominal ( r =−0.96) aortic segments as well. In patients with permanent pacemaker, wide QRS rhythm led to a significant reduction in serum matrix metalloproteinase‐9 levels (from 142.5±32.9 pg/mL to 87.5±32.4 pg/mL [ P <0.001]) at the end of 3 weeks follow‐up. Conclusions: QRS prolongation by short AVD dual pacing, dual sensing, and dual response to sensing results in concomitant decreases in peak dP/dt values in the LV and in all aortic segments with or without background beta‐blocker administration, which in turn led to a significant reduction in circulating matrix metalloproteinase‐9 levels. Registration: URL: https://www.clini​caltr​ials.gov ; Unique identifier: NCT03665558.